Digital transformation in food supply chains: a review and implementation roadmap - Wang, Shiyi; Ghadge, Abhijeet; Aktas, Emel (Emerald, 2023)
Digital transformation has gradually attracted the attention to address food supply chain (FSC) challenges. However, the integration of technologies/capabilities to achieve digital transformation in FSCs is unclear. The study aims to establish how the digital transformation of FSCs can be achieved using the Internet of Things (IoT), Cloud Computing (CC), and Big Data Analytics (BDA). A systematic literature review (SLR) is conducted to deliver a comprehensive view with 57 papers selected from 2008 to 2022. A digital transformation roadmap is proposed based on the Diffusion of Innovation (DOI) theory, which contributes to theory and practice by providing guidance for implementation.
Keywords: digital transformation; food supply chain; Internet of Things; cloud computing; big data analytics